Comparative Study of Child Soldiering on Myanmar-China Border Evolutions, Challenges and Countermeasures - Chen, Kai.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2014)
From comparative perspective, this book explores the dynamics of child soldiering on the Myanmar-China border (i.e., Kachin and Shan States of Myanmar). At the same time, this book examines the structural factors and specific relationships between child soldiers, which have impacts on child soldiering. This book reveals that Myanmar has limited power to reduce child soldiering on the Myanmar-China border, and there is no optimal solution for reducing child soldiering in the near future. Instead, the book introduces the (3z(Btransnational public-private partnership(3y (Bapproach as a (3z(Bsecond best(3y (Bsolution and proposes suitable countermeasures for all the stakeholders.s
Chapter 1 Introduction -- Chapter 2 Research Methodology -- Chapter 3 Child Soldiering on Myanmar-China Border -- Chapter 4 Structural Factors Impacting Child Soldiering -- Chapter 5 Why Children Involve in Armed Conflicts? -- Chapter 6 Why Other Children are not Recruited?Chapter 7 Transactional Public-Private Partnership: A (3z(BSecond Best(3y (BResolution -- Chapter 8 Possible Countermeasures to Reduce Child Soldiering -- Chapter 9 Outlook for Future Studies -- About the Author.s
Keywords: Political science; Comparative politics; International relations; Criminology; Political Science and International Relations; International Relations; Comparative Politics; Criminology & Criminal Justice; Electronic books